Perancagan Brand Identity Museum Loka Jala Crana Surabaya Berbasis Sejarah dan Sains Sebagai Upaya Pengenalan Laboratorium Pendidikan bagi Masyarakat - Uqba, Muhammad Tuhmadu; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
The goal of Loka Jala Crana Museum of Surabaya brand identity design is to introduce the laboratory for education to society. The design used within this thesis research is the methods of qualitative data collection which is done by conducting interview, observation, documentation, and study of existence which is very important to determine the design of the research concept. Of the data analysis result, the concept design obtained is enchant. In the next stage, the word discover is then chosen to follow the word enchant. When the term Enchanting Discovery is translated into Bahasa, it means penemuan mengagumkan, that further is taken as the concept. Enchanting is the description of learner’s curiosity on what they've been found while exploring the history at Loka Jala Crana Museum of Surabaya. Then, it becomes the strategy to introduce Loka Jala Crana Museum of Surabaya as the laboratory for education. One of them is to explore the heroic story, educate, empower, and improve the effectiveness of campaign media to schools. So that, it is expected that it can support the brand identity design introducing Loka Jala Crana Museum of Surabaya as the laboratory of education.Kata Kunci: Brand Identity, Loka Jala Crana Museum of Surabaya, History and Science, Laboratory of Education